Romanos, pero cristianos. A propósito de algunos cánones del Concilio de Elvira - Sotomayor, Manuel (Antigüedad y Cristianismo, 1990)
Being the general theme of the Congress, CHRISTINAITY AND ACULTURATION IN THE ROMAN EMPIRE, the purpose of this article is to offer some considerations on varios concepts and terminology whose use is necessary when treating these subjects and which are not always in an univocal and clear form. Besides the relations between Christianity and cultures are not completely identifiable with tose that arise between cultures in the normal process of aculturation. The Elvira Concilium offers some examples of that previously mentioned theoretically.